(untitled) (Baghdad Science Journal, 2025)
Thin filis have been prepared from the tin disulphide (SnS2 ), the pure and the doped with copper (SnS2:Cu) with a percentages (1,2,3,4)% by using ahemical spray pyrolysis techniqee on substrate of glass heated up to(603K)and sith thicknesses (0.7±0.02)?m ,after that the films were treated thermally with a low pressure (10-3mb) and at a temperature of (473K) for one hour. The influence of both doping with copper and the thermal treatment on some of the physical characteristics of the prepared films(structural and optical) was studied. The X-ray analysis showed that the prepared films were polycrystalline Hexagonal type. The optical study that included the absorptance and transmitance spectra in the weavelength range (300-900)nm demonstrated that the value of absorption coefficient (?) was greater than (104 cm-1) for the pure and doped films and that the electronic transitions at the fundamental absorption edge were of the indirect kind whether allowed or forbidden and the value of the optical energy gap in the case of the indirect transition, the allowed decreased from (2 eV) to (1.8,1.7,1.5,1.2)eV at the doping percentages (1,2,3,4)% respectively, also it was found that the value of energy gap for the pure and doped films increased after annealing. Tthe absorption and transmission spectra were used to find the optical constant including refractive index(n), extinction coefficient (k), imaginary and real part of dielectric constant (?1 &?2) , and it was found that all the optical constant was affected by changing the doping percentages; in addition to being affected after treating the films thermally